“The state has a debt to us, it ended our dreams, our life projects”: Reconstructing life projects after torture - Anne Sønneland (Torture)
Introduction: The concept of ‘life project’ is at the core of several decisions in the inter-American human rights system. The concept has also become part of the legal consciousness of torture survivors in Peru and is often referred to when they describe the impact of torture and imprisonment on their lives and on the lives of their children. Methods: The paper is based on qualitative interviews with seven Peruvian torture survivors. Results: The concept of ‘life project’ has been included in the legal consciousness of torture survivors in in Peru, and is used to address the ways in which torture and imprisonment has impacted not only on the life project of the person targeted, but also on the lives of their children. The interviewees describe damage to their life project both regarding health and the impact of stigma, but place special emphasis on the ways in which the life projects of their children have been impacted: as a result of being imprisoned, they have been unable to take care of their children for longer periods of time, their children have been subjected to violence, and they have had less access to education. Still, the interviewees describe how they reconstruct their life projects, as well as how the concept of life project serves as a starting point for demanding reparations. Discussion: The concept of “life project”, originating from the inter American Court of Human Rihgts, is useful for grasping how peoples’ lives are impacted by imprisonment and torture, and has become part of the legal consciousness of persons affected by serious and systematic human rights violations in Peru.